2019
DOI: 10.1039/c8an01696h
|View full text |Cite
|
Sign up to set email alerts
|

A carbonothioate-based far-red fluorescent probe for the specific detection of mercury ions in living cells and zebrafish

Abstract: A simple far-red fluorescent probe was developed to monitor mercury ions in environmental water samples and in living systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…The result showed that Hg 2+ could generate the cleavage of an eater group in the presence of H 2 O 2 (Scheme 2). 40…”
Section: Characteristic Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…The result showed that Hg 2+ could generate the cleavage of an eater group in the presence of H 2 O 2 (Scheme 2). 40…”
Section: Characteristic Spectramentioning
confidence: 99%
“…Very recently, we have reported several carbonothioatebased uorescent probe for detecting Hg 2+ . These probes respectively chose the 2-(2 0 -hydroxyphenyl)benzothiazole (HBT), 39 dichlororesorun, 40 and seminaphthorhodauor 41 as the uorophores, and a carbonothioate moiety was used as the recognition receptor. All these showed quick response and high selectivity for detecting Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent probes have attracted much attention owing to their outstanding sensitivity and unique bioimaging applications in live cells. [9][10][11][12] To date, although many uorescent probes for HOCl have been explored, most of them cannot specically detect intracellular basal HOCl because of their delayed response, and unsatisfactory sensitivity and selectivity. Additionally, most of the available probes possess poor water solubility, which hinders their bioimaging applications.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Fluorescence detection technology has attracted much attention for its advantages as follows: high spatial and temporal resolution, low cost and high sensitivity. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] It has been widely used in biological science, new drug development and clinical disease diagnosis. Many probes were designed and synthesized to detect biothiols through different chemical reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%